The Macroeconomic Impacts of Counterpart Funds. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper analyzes the macroeconomic impacts of the creation, accumulation, and use of counterpart funds. It draws attention to the importance of including counterpart funds in the design of macroeconomic policies to ensure their consistency. It shows that the creation or accumulation of counterpart funds in most cases is deflationary while their uses are inflationary. One conclusion is that 'untied' counterpart funds are more appropriate for countries implementing an adjustment program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet